Inhibitory effects of fermented Ougan (Citrus reticulata cv. Suavissima) juice on high-fat diet-induced obesity associated with white adipose tissue browning and gut microbiota modulation in mice. Issue 19 (23rd August 2021) - Guo, Xiao; Cao, Xuedan; Fang, Xiugui; Guo, Ailing; Li, Erhu
Abstract : In this study, Ougan juice (OJ) and lactic acid bacteria fermented Ougan juice (FOJ) were investigated individually for their capability of preventing obesity in high-fat diet (HFD)-fed C57BL/6J mice. Abstract : In this study, Ougan juice (OJ) and lactic acid bacteria fermented Ougan juice (FOJ) were investigated individually for their capability of preventing obesity in high-fat diet (HFD)-fed C57BL/6J mice. After being administered with OJ or FOJ for 10 weeks, the body weight gain, hyperlipidemia, and gut microbiota dysbiosis of HFD-fed mice were examined. The results showed that OJ or FOJ supplementation inhibited weight gain, lowered fat accumulation, reduced liver steatosis, improved glucose homeostasis and insulin sensitivity, increased brown adipose tissue (BAT) activity, and promoted white adipose tissue (WAT) browning. Both OJ and FOJ additions increased the diversity of gut microbiota. OJ reduced the relative abundance of phylum Erysipelatoclostridiaceae and genus Erysipelatoclostridium and remarkably increased SCFA-producing bacteria Blautia, while FOJ reduced the ratio of Firmicutes to Bacteroidetes and enhanced the relative abundance of family Lactobacillaceae . Spearman's correlation analysis revealed that Akkermansia, Dubosiella, and Muribaculaceae were significantly negatively correlated with obesity-related indexes. In general, FOJ exhibited a better inhibitory effect on obesity than OJ, and the possible inhibitory mechanism lies in promoting WAT browning and increasing intestinal probiotics. This study provides the guidance for developing fermented Ougan juice as an obesity-inhibiting functional food.